Financial Literacy and Gender Dynamics in Shaping Inclusive Finance - Faizan, Muhammad; Ahmad, Ishtiaq; Urooj, Javeria (UW Journal of Management Sciences, 2025)
Purpose: The growing concern on financial inclusion around the world, highlighted the focus on financial literacy. The objective of the study is to the understand the difference between the financial knowledge amongst man and woman to examine how this difference impact the use and access of financial services ultimately contributed towards the financial inclusion. This study is to serves the United Nation Sustainable Goals (SDGs) mainly SDG-1, SDG-5, SDG-8, SDG-10 and SDG-17. Design and Methodology: The study utilizes the quantitative approach with secondary data from sources such as, World bank, Findex survey, UNESCO. Panel data is used to analyze the influence by employing different panel regression techniques such as fixed-random effect model along with other measure of multicollinearity and correlation analysis. Findings: The results show significant negative relationship between gender gap in financial literacy and financial inclusion. This shows that women have low level of financial literacy as compared to the men makes it difficult for women to participate in financial system and negatively influenced their financial inclusion. Our finding highlights the importance to increase financial literacy among women to enable them effectively use financial services and to take part in financial decision making for betterment of economic empowerment. Implications: The study finding offers meaningful insights for education sector, financial institution, policy maker and government to develop different kinds of programs to enhance the financial knowledge in women in order to reduce the gender differences. These will also help in achieving Sustainable Development Goals by encouraging the gender equality, reducing inequality and encourage economic growth. Originality/Value: The study examines the relationship between financial literacy and financial inclusion in context of emerging/ developing countries.